A novel nuclear factor Akirin regulating the expression of antimicrobial peptides in Chinese mitten crab Eriocheir sinensis. (December 2019) - Yang, Wen; Liu, Chao; Xu, Qingsong; Qu, Chen; Lv, Xiaojing; Li, Huan; Wu, Zhaojun; Li, Meijia; Yi, Qilin; Wang, Lingling; Song, Linsheng
Abstract: Akirin, a recently discovered nuclear factor, participates in regulating various processes, including cell proliferation and differentiation, embryonic development, and immunity. In the present study, a novel Akirin was identified from Chinese mitten crab Eriocheir sinensis (designated as Es Akirin), and its primary functions in regulating antimicrobial peptides were explored. The open reading frame of Es Akirin was of 615 bp, encoding a polypeptide of 204 amino acid residues. The deduced amino acid sequence of Es Akirin shared high similarities ranging from 44.1% to 89.2% with other Akirins. In the phylogenetic tree, Es Akirin was firstly clustered with Akirins from shrimp and then assigned into the invertebrate branch. The mRNA transcripts of Es Akirin were constitutively expressed in all the tested tissues, with the highest expression level (5.07-fold compared to the stomach, p  < 0.01) in hepatopancreas. The mRNA expression of Es Akirin in hemocytes was significantly increased at 6 h, and reached the maximum level at 24 h post stimulations with either lipopolysaccharide (LPS) (5.04-fold, p  < 0.01) or Aeromonas hydrophila (3.10-fold, p  < 0.01). After the injection of Es Akirin-dsRNA, the mRNA expressions of Es ALF2, Es LYZ, Es Crus2 and Es DWD1 were significantly decreased ( p  < 0.01) upon LPS stimulation. Es Akirin protein was prominently distributed in the nucleus of E. sinensis hemocytes after LPS and A. hydrophila stimulations. The relative luciferase reporter system analysis revealed that the activity of nuclear factor-κB was significantly up-regulated (2.64-fold, p  < 0.01) in human embryonic kidney (HEK293T) cells after the over-expression of Es Akirin. Collectively, these results suggested that Es Akirin might play an important role in the immune responses of E. sinensis by regulating the expression of antimicrobial peptides. Highlights: Es Akirin was a homolog of invertebrate Akirin in Eriocheir sinensis. The expression of Es Akirin increased after LPS and A. hydrophila stimulations. Es Akirin regulated the expressions of Es ALF2, Es LYZ, Es Crus2 and Es DWD1 post LPS stimulation. Es Akirin could enhance the luciferase activity of NF-κB in HEK293T cells.